The Audio Description of a Spanish Phenomenon: Torrente 3 - Wharton, Steve; Orero (The Journal of Specialised Translation, 2007)
While audio description as a technique has been round for centuries, its research in academia has just started. In some countries, such as Spain, norms and standards have been officially drafted before taking into consideration any scientific research results.This paper analyses some of the widely available audio description style sheets in Europe and the USA through a practical case: the creation of the audio description for the infamous Spanish film Torrente 3.